2005
DOI: 10.1111/j.1365-2044.2005.04258.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial anatomic investigations of the I‐gel airway: a novel supraglottic airway without inflatable cuff*

Abstract: SummaryThe I-gel airway is a novel supraglottic airway that uses an anatomically designed mask made of a gel-like thermoplastic elastomer. We studied the positioning and mechanics of this new device in 65 non-embalmed cadavers with 73 endoscopies (eight had repeat insertion), 16 neck dissections, and six neck radiographs. A full view of the glottis (percentage of glottic opening score 100%) occurred in 44 ⁄ 73 insertions, whereas only 3 ⁄ 73 insertions had epiglottis-only views. Including the eight repeat inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
190
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 15 publications
5
190
1
1
Order By: Relevance
“…(23,24) The i-gel SAD has a non-inflatable cuff that was designed to provide an anatomical fit over the perilaryngeal structures, minimising the risk of compression of neurovascular structures in these tissues and thereby reducing the incidence of airway complications. (25,26) Our study had several limitations. Firstly, it was unblinded, as the investigators could not be blinded during airway management, hence presenting the possibility of researcher bias.…”
Section: Discussionmentioning
confidence: 99%
“…(23,24) The i-gel SAD has a non-inflatable cuff that was designed to provide an anatomical fit over the perilaryngeal structures, minimising the risk of compression of neurovascular structures in these tissues and thereby reducing the incidence of airway complications. (25,26) Our study had several limitations. Firstly, it was unblinded, as the investigators could not be blinded during airway management, hence presenting the possibility of researcher bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study using a cadaver model, the oesophageal seal pressure of the i-gel TM was found to be significantly lower than with the Classic TM and ProSeal TM laryngeal masks 20 . In initial investigations performed on cadavers it was found that the i-gel TM effectively mirrored the perilaryngeal anatomy and that it consistently achieved positioning for supraglottic ventilation 21 . The device was designed after investigation using cadaveric dissections, endoscopies and radiological imaging in an attempt to ensure the cuff mirrored the pharyngeal, perilaryngeal and laryngeal anatomy.…”
mentioning
confidence: 99%
“…The bowl enlarges slightly in width but more significantly in height. 6 Levitan and Kinkle studied the positioning of i-gel in 65 non-embalmed cadavers using glidoscope video laryngoscope, block dissection of neck and neck radiographs in lateral view. 6 They found that the i-gel effectively conformed to the perilaryngeal anatomy despite the lack of an inflatable cuff and it consistently achieved proper positioning for supraglottic ventilation.…”
Section: Discussionmentioning
confidence: 99%